Psychometric properties of the post-stroke depression scale in the sequelae stage - Zeng, Yawei; Li, Fengzhen; Ning, Liuqiao; Fu, Yingjie; Ge, Yajing; Gan, Beibei; Lin, Suichai; Lin, Haiyun; Li, Jufang (Frontiers in Psychology, 2023)
Abstract Aim: To evaluate the psychometric properties of the Post-Stroke Depression Scale in the Sequelae Stage (PSDS-SS). Background：The incidence of the sequelae stage Post-Stroke Depression (PSD) is high, and the best screening tools are still lacking. Under this circumstances, our research team developed the PSDS-SS by Delphi method, but its psychometric properties need to be further verified. Method: This was a cross-sectional study. Seven hundred and sixteen stroke patients in the sequelae stage were enrolled by purpose sampling from May 2022 to September 2022. The exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to verify the factor structure of the scale. The reliability of the scale was tested by Cronbach’s α coefficient, test-retest reliability and composite reliability. The validity of the scale was tested by criterion-related validity, convergent and discriminant validity. Result: Eight items were deleted through item analysis. The EFA ended up with a 5-factor scale including 24 items after removing one item with low factor loading. Finally, a 21-item model was established by confirmatory factor analysis, and all the fit indexes were acceptable. The reliability and validity of the total scale and each factor are acceptable. Conclusion: The PSDS-SS has a stable factor structure, and demonstrated good reliability and validity. And it would be an effective tool to assess PSD in the sequelae stage.